Hybridizing solar dish Stirling power system with single-effect desalination for sustainable electricity and freshwater co-generation: Mathematical modeling and performance evaluation. (May 2023) - Alhawsawi, Abdulsalam; Zayed, Mohamed E.; Moustafa, Essam; Banoqitah, Essam; Elsheikh, Ammar H.
Abstract: At present, poly-generation sustainable systems are highly promising pathways that could produce several beneficial energy outputs, such as electricity, heat, and freshwater, that have the potential to fulfill financial competitiveness and higher efficiencies. Considering the great advantages of the solar dish/Stirling cycle, this study introduces comprehensive theoretical modeling and performance analysis of a solar dish/Stirling-powered single effect distillation system (SDSPSEDS) for combined electricity, heat, and freshwater tri-production. A detailed mathematical model executed in MATLAB software based on energy balance and opt-geometric approaches was established to simulate the SDSPSEDS operation dynamically. In order to analyze its performance under real weather conditions of Tabuk, KSA, for four seasonal scenarios. The energetic performance of the hybrid SDSPSEDS is comprehensively evaluated in terms of net electric power, solar-to-electricity conversion efficiency, Stirling engine rejected heat, distilled freshwater productivity, and overall co-generation efficiency of the hybrid system. The simulation results show that the daily electrical energy produced by the SDSPSEDS is 234.7, 194.6, 159.8, and 190.0 kWh/day. In contrast, the daily freshwater production is obtained as 787.4, 657.3, 545.0, and 650.0 kg/day in June, September, January, and March, respectively. Moreover, it is also found that the overall daily co-generation efficiency of the hybrid SDSPSEDS is increased to 62.60%, 53.50%, 47.40%, and 52.96% compared to only daily average electrical efficiencies of 20.92%, 17.82%, 15.50%, and 17.60% attained; in the same examined seasonal days, respectively when utilizing only standalone solar dish/Stirling power system. Thus, the findings of this study proved that the hybrid SDSPSEDS is an efficient system to produce power and water in rural areas with no water piping network or electrical grid.